Perancangan Aplikasi Kompresi File PDF Dengan Menerapkan Algoritma Golomb - Yeni Anggraini (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Currently, many people from companies and universities use the PDF file format to provide all available information because it is considered faster and when it is sent it will not change the format when it is opened on another device. However, sometimes it will save a PDF file that affects the computer's performance too much. With these problems, a data compression technique is needed to reduce the size of the existing PDF files, in order to save more storage space.Compression is a process of reducing or differentiating a data size to be smaller than the sleeping one. Data compression is very helpful where there is a large amount of data and it contains many characters. Compressing PDF files can help in better management, and is very helpful in fast file transfers. In designing this compression application, the Golomb algorithm is used to perform the compression and decompression processes.As for the final result of the compression process using algorithm Golomb by the author, the results of the performance parameters are Ratio of Compression of 2.27, Compression Rate of 44.14%, Redundancy of 55.86% and Space Saving of 55.86%. The initial size of the PDF file which is compressed by applying the Golomb algorithm is reduced to 44.14% of the PDF file size, which means it supports